Corruption and Age - Benno Torgler; Neven T. Valev (Center for Research in Economics, Management and the Arts (CREMA), 2004)
In recent years the topic of corruption has attracted a great deal of attention. However, there is still a lack of substantial empirical evidence about the determinants of corruption. This empirical study analyses a cross-section of individuals using the World Values Survey wave III (1995-1997), investigating the justifiability of corruption. The major aim in the paper is to investigate whether we observe differences between age groups. Despite an increasing interest of economists in the determinants of corruption, the factor age has been widely neglected in the literature. The results suggest that there is a strong age effect, controlling in a multivariate analysis for additional factors.
Keywords: H10; J16; K42; 330; Corruption; Age; Bribe; Social Norms